'What is it called in Spanish?': Parallel Monolingualisms and translingual classroom talk. Issue 3 (2nd October 2019) - Jonsson, Carla
ABSTRACT: In a bilingual school, the linguistic and semiotic resources of students who speak one, two or several languages can be used in classroom discourse in order to embrace and strengthen the multiplicity of voices and languages in teaching and learning. In this article, four English language lessons – where the medium of instruction mainly oscillates between Swedish and English, and where Spanish is also used – are analysed with the aim of generating knowledge about how translanguaging is or could be used as a pedagogical resource in the classroom. The data were collected through ethnographic fieldwork in a 5th grade class at a bilingual school in the Stockholm area and consist of recordings of classroom observations, photos and field notes.